Nonoverlapping Domain Decomposition Method with Mixed Element for Elliptic Problems (Journal of Computational Mathematics, 2021)
In this paper we consider the nonoverlapping domain decomposition method based on mixed element approximation for elliptic problems in two dimensional space. We give a kind of discrete domain decomposition iterative algorithm using mixed finite element, the subdomain problems of which can be implemented parallelly. We also give the existence, uniqueness and convergence of the approximate solution.